2001
DOI: 10.1099/0022-1317-82-9-2279
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Autographa californica multiple nucleopolyhedrovirus ODV envelope protein p74 using a GFP tag

Abstract: The Autographa californica multiple nucleopolyhedrovirus (AcMNPV) protein p74 is associated with the occlusion-derived virus (ODV) envelope. p74 is essential for oral infectivity of ODV and has been proposed to play a role in midgut attachment and/or fusion. In this study, p74 protein was expressed in-frame with green fluorescent protein (GFP) to create a p74-GFP chimera. The Cterminal GFP portion of the chimera facilitated visualization of the trafficking of p74 in baculovirusinfected Spodoptera frugiperda (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…In previous studies, a number of ODV-associated proteins, including P91 and ODV-E25, were shown to be localized around the periphery of the nucleus (Russell & Rohrmann, 1997;Braunagel et al, 1999;Rosas-Acosta et al, 2001;Slack et al, 2001). These distributions are in sharp contrast to the location of the IE1-associated structure that often occupies the central region of the nucleus at 24 h p.i.…”
Section: Two Odv-associated Proteins P91-gfp and Gfp-odv-e25 Become mentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies, a number of ODV-associated proteins, including P91 and ODV-E25, were shown to be localized around the periphery of the nucleus (Russell & Rohrmann, 1997;Braunagel et al, 1999;Rosas-Acosta et al, 2001;Slack et al, 2001). These distributions are in sharp contrast to the location of the IE1-associated structure that often occupies the central region of the nucleus at 24 h p.i.…”
Section: Two Odv-associated Proteins P91-gfp and Gfp-odv-e25 Become mentioning
confidence: 93%
“…In studies examining the intracellular localization of viral proteins by fluorescent microscopy, a number of ODVassociated proteins (e.g. ODV-E25, ODV-E66, P91 and P74) were shown to localize to the periphery of the nucleus (Russell & Rohrmann, 1997;Braunagel et al, 1999;RosasAcosta et al, 2001;Slack et al, 2001). More detailed observations with immunoelectron microscopy, however, have revealed that these proteins are mainly localized to the peristromal region in association with ODVs and intranuclear microvesicles (Russell & Rohrmann, 1993, 1997Braunagel et al, 1996a, b;Hong et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently the only baculovirus protein demonstrated to be involved in oral infectivity by ingestion of polyhedra was the ODV-specific P74 (Kuzio et al, 1989), which contains a hydrophobic C terminus involved in protein localization and transmembrane anchoring. None of the other proteins of the ODV envelope, such as ODV-E18, -EC27, -E35, -E25, -E56 and -E66, were proven to participate in the oral infectivity process (Slack et al, 2001). Recently, however, a conserved baculovirus gene encoded by ORF7 of Spodoptera littoralis nucleopolyhedrovirus (SpliNPV) was also found to be required for the oral infection of S. littoralis.…”
Section: Introductionmentioning
confidence: 99%
“…The plasmids, pBAC-5-EGFP and pBAC-5-p74-EGFP, were previously described as pBAC-5-GFP and pBAC-5-p74-GFP (Slack et al, 2001). pBAC-5-p74-EGFP contains the AcMNPV p74 ORF fused at the 39 end in-frame with the jellyfish EGFP ORF (Zhang et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…2a). These plasmids were previously used to study P74 localization in infected cells (Slack et al, 2001). Though designed as baculovirus shuttle vectors, pBAC-5-based plasmids are excellent for transient gene expression in insect cell culture (Ogay et al, 2006), due to the presence of an AcMNPV gp64 early/late promoter (Whitford et al, 1989;Blissard & Rohrmann, 1991).…”
Section: Development Of a Transient Expression-based Assay For Characmentioning
confidence: 99%